1970
DOI: 10.1021/ma60013a019
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Properties of a Model Reinforced Elastomer. Styrene-Butadiene Reinforced with Polystyrene

Abstract: where i\ is the volume fraction of the solvent in the ternary system, given by r, = xanj(xan, + xph + xahUh) Then, total polymer concentration at the critical point, C0, is given by C" = 1 -(f3)wi. = (1 + l¡V~ry/(2xpA) (7) Equation 7 may predict the compatibility of the A-Btype block copolymer with the B polymer in a solution of common solvent as a function of the ratio of the degrees of polymerization, r, the composition of the block copolymer, ipA, and the copolymer-homopolymer interaction parameter, .Conseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

1973
1973
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(27 citation statements)
references
References 0 publications
1
26
0
Order By: Relevance
“…Dynamic mechanical testing is a common technique to study the effect of particles on the T g of polymers, [11][12][13][14][15][16][17][18][19][20][21][22][23] and a summary of these studies is given in Table I. Many investigators draw conclusions based on the temperature of the maximum in the isochronal loss tangent, tanδ = G"/G' (abbreviations are defined in the appendix).…”
Section: Dynamic Mechanical Spectroscopymentioning
confidence: 99%
“…Dynamic mechanical testing is a common technique to study the effect of particles on the T g of polymers, [11][12][13][14][15][16][17][18][19][20][21][22][23] and a summary of these studies is given in Table I. Many investigators draw conclusions based on the temperature of the maximum in the isochronal loss tangent, tanδ = G"/G' (abbreviations are defined in the appendix).…”
Section: Dynamic Mechanical Spectroscopymentioning
confidence: 99%
“…The extent to which these localized effects translate into modification of the viscoelastic T g of the bulk polymer is unclear. Dynamic mechanical testing is often employed to study the impact of particles on the T g of polymers, [2][3][4][5][6][7][8][9][10][11] but many of these studies draw conclusions based on the isochronal loss tangent (tan δ ) G′′/G′) vs temperature peak that occurs near the glass transition. This can be problematic because tan δ in the glass-to-rubber softening region is influenced not only by local segmental motions, as reflected in the loss modulus (G′′) toward lower T, but also by filler reinforcement effects on both the storage modulus (G′) and G′′ at higher T. In this paper we illustrate this through detailed viscoelastic characterization of carbon black-filled polybutadiene and poly(styrene-co-butadiene) reinforced with silica particles.…”
Section: Introductionmentioning
confidence: 99%
“…According to the nuclear magnetic resonance (NMR) investigations on CB‐filled ethylene–propylene rubber (EPDM) compounds made by Kaufman [26], in close vicinity to the CB surface within 1 nm there is a thin layer of polymer whose mobility is extremely restricted due to the interaction with the CB surface. This polymer layer consists of two components, a relatively mobile component in the middle and an immobilized one next to each filler aggregate surface [26, 27]. A literature study pointed out that the thickness of the immobilized layer actually depends on the polymer–filler interaction [28].…”
Section: Resultsmentioning
confidence: 99%
“…The rigidity of the network is characterized by a specific glass temperature of the immobilized layer T Gil, exceeding it the immobilized layer becomes mobile, and the network looses its reinforcement effect. The immobilized layer of 1.0 nm thickness closed to the CB surface in the CB filled EPDM compounds has a T Gil of about 100°C and it decreases toward the middle region [27]. By means of a new method, the thermally scanning stress relaxation, on filled elastomers, Srinivasan et al [33] found that an increase in temperature would further aid in weakening filler–filler bonds.…”
Section: Resultsmentioning
confidence: 99%